Organizational learning in China: the role of returners - Ariane Berthoin Antal; Jing Wang (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
The Chinese authorities have launched a range of policies and incentives at the national and regional level to attract citizens who have studied and worked abroad to return in order to contribute to upgrading the competitiveness of the Chinese economy, particularly in light of China's entrance to the World Trade Organization. In other words, the returners are expected to stimulate organizational learning in existing organizations and in new companies. This article provides an overview over what has been done to date and points out that simply increasing the number of returners is not enough to achieve organizational learning. Drawing on research findings about the dynamics of organizational learning from returned expatriate managers in international companies, the article develops recommendations for government policies, corporate strategies and Chinese returners. – – In den letzten Jahren hat die chinesische Regierung vielfältige Maßnahmen eingeleitet, um chinesische Bürger, die im Ausland studiert und gearbeitet haben, zur Rückkehr zu bewegen, um mit deren Wissen die Konkurrenzfähigkeit der Wirtschaft des Landes zu stärken. Diese Transformationsaufgabe, die durch den WTO Beitritt Chinas als dringend angesehen wird, erfordert umfangreiche Organisationslernprozesse. Der vorliegende Beitrag bietet einen Überblick über die Palette der bisherigen Maßnahmen und weist darauf hin, dass eine rein quantitativ ausgerichtete Politik kein Garant für den nötigen Grad an Organisationslernen ist. Aufbauend auf Forschungsergebnissen über Organisationslernen durch Expatriates in multinationalen Unternehmen, werden Empfehlungen für die staatliche Politik, für Unternehmen und für die Rückkehrer ausgearbeitet.
Keywords: 300; Lernende Organisation; China; Auslandsaufenthalt